Developmental Roles of AUX1/LAX Auxin Influx Carriers in Plants - Swarup, Ranjan; Bhosale, Rahul (Frontiers in Plant Science, 2019)
Plant hormone auxin regulates several aspects of plant growth and development. Auxin is predominantly synthesized in the shoot apex and developing leaf primordia and from there it is transported to the target tissues e.g. roots. Auxin transport is polar in nature and is carrier-mediated. AUXIN1/LIKE-AUX1 (AUX1/LAX) family members are the major auxin influx carriers whereas PIN-FORMED (PIN) family and some members of the P-GLYCOPROTEIN/ ATP-BINDING CASSETTE B4 (PGP/ABCB) family are major auxin efflux carriers. AUX1/LAX auxin influx carriers are multi-membrane spanning transmembrane proteins sharing similarity to amino acid permeases. Mutations in AUX1/LAX genes result in auxin related developmental defects and have been implicated in regulating key plant processes including root and lateral root development, root gravitropism, root hair development, vascular patterning, seed germination, apical hook formation, leaf morphogenesis, phyllotactic patterning, female gametophyte development and embryo development. Recently AUX1 has also been implicated in regulating plant responses to abiotic stresses. This review summarizes our current understanding of the developmental roles of AUX1/LAX gene family and will also briefly discuss the modelling approaches that are providing new insight into the role of auxin transport in plant development.